2015
DOI: 10.5799/ahinjs.02.2015.01.0165
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Leptospira antibodies among populations at risk

Abstract: Objective: This study was performed to assess the Leptospira IgG antibodies seroprevalence among populations at risk in Hodeida Governorate, Yemen.Methods: A total of 200 subjects (136 males and 64 females) participated in this study during June and December 2012.They represented 10 sewage workers, 22 butchers, 16 construction workers, 108 agriculture workers, 20 hospital sanitary workers and 24 blood donors. Predesigned questionnaires and consent were taken from each individual. Blood samples were collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…The total seroprevalence of leptospirosis according to positive Leptospira IgG antibodies (cut off > 30 IU/ml) in our study group was 41.3%. This result is similar to previously seroprevalence studies reported in Yemen Hodeida in which the rate was 42% 3 . Also similar findings were demonstrated in studies conducted in Thailand: 12.7-40% 8 , in Indonesia: 37% 9 .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The total seroprevalence of leptospirosis according to positive Leptospira IgG antibodies (cut off > 30 IU/ml) in our study group was 41.3%. This result is similar to previously seroprevalence studies reported in Yemen Hodeida in which the rate was 42% 3 . Also similar findings were demonstrated in studies conducted in Thailand: 12.7-40% 8 , in Indonesia: 37% 9 .…”
Section: Discussionsupporting
confidence: 83%
“…The possibility of get in touch with animal pathogens whilst working depends on a variety of aspects, for instance the health of the animals, the kind of job executed the incidence of make contact with animals, and/or their tissues and carcasses, the employ of personal and environmental protective measures, and the manners and levels of awareness of the people at risk 1. Slaughterhouse workers and butchers are on elevated risk of contracting zoonosis. In Yemen, previous studies have recognized zoonosis similar to leptospirosis and brucellosis, such as potential occupational hazards for slaughterhouse workers 2,3 . Leptospirosis is a widespread infections that involves both humans and animals 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is noted that the incidence is higher among the elderly aging between 60 and 74, and this can also be seen in a study conducted in Yemen where the highest prevalence rate of Leptospira IgG antibodies was found among old population of above 58 years of age. 28 In another study in Bulgaria, leptospirosis incidence among those aging from 60 to 78 constituted about 14% of their sample population and was associated with severe course and higher risk of death requiring prompt intensive treatment. 29 We noted the surge in leptospirosis incidence during the different periods of our study.…”
Section: Discussionmentioning
confidence: 98%
“…Among studies from the United Arab Emirates, one showed a seroprevalence of 4.1% [ 58 ] in camels, and another showed a seroprevalence of 1.7% in cattle [ 59 ]. In Yemen, a seroprevalence of 41.3% [ 60 ] and 42% [ 61 ] by ELISA was reported in humans, and a seroprevalence of 6.7% by SSI was reported in camels in Saudi Arabia [ 62 ].…”
Section: Resultsmentioning
confidence: 99%